Twenty Thousand Leagues East: Around the World with Nadia: The Secret of Blue Water. - McAllister, Robbie (Science Fiction Studies, 2021)
Originally conceived as an adaptation of the works of Jules Verne by Hayao Miyazaki and eventually developed by Hideaki Anno and the studio Gainax, Nadia: The Secret of Blue Water (1990-1991) acts as one of the clearest examples of the fascinating interdependencies that are evident between the Japanese entertainment industries and the movement that has become known as steampunk. Variously defined as neo-victorientalism and steampanku by those with an interest in its representations of industrial nostalgia, Japanese steampunk has served as a rich resource for representations of Japan’s past, present, and future, filtered through the iconography of fantastical steam-powered and piston-driven machinery. This article offers a close analysis of the series and considers the ways that its reworking of archetypal representations of nineteenth-century sf offer opportunities to evaluate the enormously complex and contradictory facets of nostalgic reminiscence. By considering the ways that the series fetishizes referents to this past age of technological development, I evaluate the means through which a legacy of bygone scientific romance and imperial adventure continues to reflect the fin-de-siècle concerns of a later century and Japan’s own orientation in a globalized and postcolonial world.